2011
DOI: 10.1111/j.1476-5381.2011.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of opioid and cannabinoid receptor blockade on heroin‐seeking reinstatement and cannabinoid substitution in heroin‐abstinent rats

Abstract: BACKGROUND AND PURPOSEOpioids and cannabinoids interact in drug addiction and relapse. We investigated the effect of the opioid receptor antagonist naloxone and/or the cannabinoid CB1 receptor antagonist rimonabant on cannabinoid-induced reinstatement of heroin seeking and on cannabinoid substitution in heroin-abstinent rats. EXPERIMENTAL APPROACHRats were trained to self-administer heroin (30 mg·kg -1 per infusion) under a fixed-ratio 1 reinforcement schedule. After extinction of self-administration (SA) beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
0
10
1
Order By: Relevance
“…One approach to identifying potential therapies for ICD in PD is by analogy to impulsivity and addiction not associated with PD, given the similarities in behavioral manifestations and anatomic substrates, although limitations are present in such extrapolations. For instance, non‐PD impulsivity or addiction studies in animals, and genetic studies, suggest involvement of mu opioid, cannabinoid, nicotinic, and D4 dopamine systems . Although recognizing that data on pre‐clinical efficacy obtained in models with an intact dopaminergic system may not be predictive of ICDs in PD patients who have dopaminergic systems affected by the disease process is important, these data identify potential therapeutic targets for PD ICDs.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
“…One approach to identifying potential therapies for ICD in PD is by analogy to impulsivity and addiction not associated with PD, given the similarities in behavioral manifestations and anatomic substrates, although limitations are present in such extrapolations. For instance, non‐PD impulsivity or addiction studies in animals, and genetic studies, suggest involvement of mu opioid, cannabinoid, nicotinic, and D4 dopamine systems . Although recognizing that data on pre‐clinical efficacy obtained in models with an intact dopaminergic system may not be predictive of ICDs in PD patients who have dopaminergic systems affected by the disease process is important, these data identify potential therapeutic targets for PD ICDs.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
“…CB1 receptor agonist-induced amnesic effects and memory consolidation are notably impaired by morphine activation of MORs, which are also the mediators of many of the central neural effects produced by enkephalin [10;48]. Moreover, cannabinoid abuse increases one's likelihood of developing opiate addiction and vice versa [11-13]. Prenatal and adolescent exposure to THC can also increase heroin-seeking tendencies in adults [9;38;41].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with results from previous studies, which showed that morphine is effective at reactivating opiate‐seeking behaviour in mice and that the CPP paradigm is useful for investigating mechanisms underlying relapse of drug abuse (Martin et al ., ; Ribeiro Do Couto et al ., ). Interestingly, drug‐seeking behaviour associated with a variety of abused substances can be reinstated or attenuated following CB 1 receptor activation or antagonism respectively (De Vries et al ., ; Alvarez‐Jaimes et al ., ; Fattore et al ., ). However, how the eCB system affects drug‐related addiction behaviours was unclear.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that mice lacking CB1 receptors (CB1 knockouts) fail to exhibit conditioned place preference (CPP) with morphine (Martin et al, 2000) and do not acquire morphine self-administration (Ledent et al, 1999;Cossu et al, 2001). In addition, activation of CB1 receptors has been shown to reinstate heroin-seeking behaviour (De Vries et al, 2003;Fattore et al, 2011), whereas blockade of CB1 receptors in a related region attenuates cue-induced heroin-seeking behaviour (Alvarez-Jaimes et al, 2008). However, how the eCB system affects drug-related addiction behaviours remains unclear.…”
Section: Introductionmentioning
confidence: 99%